Black-White Differences in the Relationship between Parental Income and Depression in Young Adulthood: The Different Roles of Family Support and College Enrollment among U.S. Adolescents. Issue 4 (October 2019) - Park, Kiwoong
This study uses the National Longitudinal Study of Adolescent to Adult Health to examine racially patterned mechanisms linking parental income and early adult depression, focusing on the mediating roles of family support and college enrollment. Findings suggest two noteworthy Black-White differences. First, parental income is positively correlated with depression for Black adolescents through family support. This is because high parental income tends to decrease family support for Black adolescents, a pattern not replicated for White adolescents. Second, college enrollment mediates the relationship between parental income and adult depression for Whites but not Blacks. This is because Black respondents in high-income families tend to have lower chances of college enrollment than their White counterparts, and this also leads to unequal mental health benefits for highly educated Blacks. These results, framed within a life-course perspective, provide insights about how the pathways from class to mental health are shaped by race.